Two modes of interfacial pattern formation by atmospheric pressure helium plasma jet-ITO interactions under positive and negative polarity. (18th April 2017) - Liu, Zhijie; Liu, Dingxin; Xu, Dehui; Cai, Haifeng; Xia, Wenjie; Wang, Bingchuan; Li, Qiaosong; Kong, Michael G
Abstract: In this paper, we report the observation of an interfacial pattern formation on the ITO surface by atmospheric pressure helium plasma jet-ITO interactions. By changing the voltage polarity of positive and negative pulses, the interfacial phenomenon displays two different pattern modes, i.e. a double ring pattern with a combination of homogeneous and filamentous modes as well as a single ring pattern with a homogeneous mode. The reasons may mainly be attributed to the spread of a radially outward traveling surface ionization wave that would cause electric field distributions and charge accumulations on the ITO surface. The spatial-temporal distribution of N 2 + ( B 2 ∑ u + ), He(3s 3 S), and O(3p 5 P) emissions are diagnosed to better understand the formation mechanism and the differences of plasma jet patterns under positive and negative polarities. Results show that the distribution of N 2 + ( B 2 ∑ u + ) emission is the main contributor for generating the filament structure in a double ring pattern for positive polarity, the homogeneous mode pattern mainly depends on the distribution of O(3p 5 P) emission for positive and negative polarity. Additionally, in order to further systematically understand the behaviors of plasma jet patterns, some parametric results, such as behaviors versus pulse peak voltage, dielectric material, pulse repetition rate, and flow rate are investigated. Some interesting phenomena and additional insights for the plasma jet pattern are found with different parametric conditions. This study might help to better understand effects of plasma jets in interaction with surfaces, or its application in the medical sector.